Reduced intensity-conditioned allogeneic stem cell transplantation for multiple myeloma relapsing or progressing after autologous transplantation: a study by the European Group for Blood and Marrow Transplantation - Auner, Holger; Szydlo, R.; van Biezen, A.; Iacobelli, S.; Gahrton, G.; Milpied, N.; Volin, L.; Janssen, J.; Nguyen Quoc, S.; Michallet, M.; Schoemans, H.; el Cheikh, J.; et al. (Bone marrow transplantation, 2013)
Outcomes and prognostic factors of reduced intensity-conditioned allo-SCT (RIC allo-SCT) for multiple myeloma (MM) relapsing or progressing after prior autologous (auto)-SCT are not well defined. We performed an analysis of 413 MM patients who received a related or unrelated RIC allo-SCT for the treatment of relapse/progression after prior auto-SCT. Median age at RIC allo-SCT was 54.1 years, and 44.6% of patients had undergone two or more prior auto-SCTs. Median OS and PFS from the time of RIC allo-SCT for the entire population were 24.7 and 9.6 months, respectively. Cumulative non-relapse mortality (NRM) at 1 year was 21.5%. In multivariate analysis, CMV seronegativity of both patient and donor was associated with significantly better PFS, OS and NRM. Patient-donor gender mismatch was associated with better PFS, fewer than two prior auto-SCT was associated with better OS, and shorter time from the first auto-SCT to the RIC allo-SCT was associated with lower NRM. The results of this study identify patient and donor CMV seronegativity as the key prognostic factor for outcome after RIC allo-SCT for MM relapsing or progressing after prior auto-SCT.
Gesehen am 23.10.2020